Disability, globalization and human rights - Katsui, Hisayo; Chalklen, Shuaib (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"The UN Convention on the Rights of Persons with Disabilities has facilitated the understanding that disability is both a human rights and development issue. In order to achieve the Sustainable Development Goals by 2030, the focus on disability inclusion has become increasingly important in the discourse of international and national efforts for "leaving no one behind", the motto of the SDGs. This book discusses pertinent and emerging themes such as disability rights, globalization, inequalities, international cooperation and representation. Co-edited by a disability researcher and the former United Nations Special Rapporteur on Disability, this book will be of interest to all students, academics, policy makers and practitioners working to advance the cause of disability rights around the world"--
OCLC-licensed vendor bibliographic record.
Keywords: People with disabilities -- Civil rights; Human rights; Sustainable development; LAW / Disability; SOCIAL SCIENCE / Social Work; SOCIAL SCIENCE / Sociology / General